(untitled) (Palíndromo, 2023)
When conceiving a fertile ground marked by the conflict between reality and fantasy, the Mexican director Guillermo del Toro expands the fantastic universe by producing the feature film Pan’s Labyrinth, in 2006. The film, notable for mixing the world of dreams with the real world, is structured in the context of the Francoist dictatorship, in Spain, bringing the story of a dreamy young girl, Ofélia. Throughout the plot, the protagonist’s narrative alternates between the drama of a reality marked by violence and a dark fairy tale, full of strangely seductive grotesque creatures that flirt with the notion of unheimlich, proposed by Sigmund Freud. From this, this article intends to articulate the aesthetic conception of estrangement proposed by Freud to the theories of the grotesque, using them as a reading key for Del Toro’s work. From the perspective of the Freudian unheimlich, we sought to explore aspects of the film that corroborate the apprehension of the grotesque through restlessness.